Sociodiscursive representations about leprosy in educational campaigns: implications on stigma reduction - Elis Oliveira Arantes; Francisco Carlos Félix Lana (Associação Brasileira de Enfermagem, 2022)
ABSTRACT Objectives: to analyze the socio-discursive representations about leprosy produced in posters of educational campaigns of the Brazilian Ministry of Health. Methods: a documentary and discursive research about posters of campaigns about leprosy produced by the Brazilian Ministry of Health and available on Google Search Images. For the analysis, we used the Critical Discourse Analysis approach and the Grammar of Visual Design. Results: the socio-discursive representations of leprosy are based on the biomedical ideology, through a normative-curative discourse that focuses on the dermatological manifestations of the disease. Regarding the construction of the compositional space, there are posters that emphasize the meaning that the disease does not prevent affectionate relationships, and others highlight as "new" the clinical manifestations of the disease. Final Considerations: the normative-curative discourse produced in the campaigns is not enough to face stigma related to the disease. For leprosy to be understood as a common chronic disease, it is first necessary to fight the "social leprosy": the stigma.